ChemInform Abstract: Direct Olefination of Alcohols with Sulfones by Using Heterogeneous Platinum Catalysts. Issue 36 (August 2016) - Siddiki, S. M. A. Hakim; Touchy, Abeda Sultana; Kon, Kenichi; Shimizu, Ken‐ichi
Abstract: Carbon‐supported Pt nanoparticles (Pt/C) are established as effective heterogeneous catalysts for the direct Julia olefination of alcohols in the presence of sulfones and KOtBu under oxidant‐free conditions.